EFEKTIFITAS METODE PEMBELAJARAN TAHSIN AL-QUR’AN TERHADAP KEMAMPUAN MEMBACA AL-QUR’AN PADA MAHASISWA/I AKPER MALAHAYATI MEDAN - MULIANI NASUTION (JURNAL ILMIAH MAKSITEK, 2023)
This study aims to determine the effectiveness of tahsin al-qur'an learning method on the ability to read al-qur'an on akper malahayati medan students. Based on interviews and documentation studies conducted in this study, it was found that tahsin learning proved effective in improving the ability to read the Qur'an. This can be seen in several indicators, namely: Good organization of material is done to find out how to sort the material to be delivered logically and regularly, so that there is a clear link between one topic and another during learning. Effective Communication that the relationship between lecturers and students who are taught is built so that there is effective communication and a fluid learning atmosphere without feeling burdened. 3. Good Student Learning Outcomes. Student learning outcomes are quite good and there is an increase in the ability to read the Qur'an. This study used an experimental method with a posttest only control design, which placed research subjects into two groups (classes) which were divided into experimental and control classes. This research was also conducted using a qualitative approach, which is a method based on the scientific method or scientific because it has fulfilled scientific rules, namely concrete / empirical, objective, measurable, rational and systematic, to obtain data using the documentation method and the test method and in analyzing the data, namely using content analysis, analyzing the contents of reading material or documents related to the research, while the data obtained through in-depth interviews and observations will be analyzed through descriptive analysis, namely the data obtained, studied, classified and analyzed in depth, then concluded. And to maintain data validity, researchers use triangulation techniques.